2x+36-2y+x+y=180

Simple and best practice solution for 2x+36-2y+x+y=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+36-2y+x+y=180 equation:


Simplifying
2x + 36 + -2y + x + y = 180

Reorder the terms:
36 + 2x + x + -2y + y = 180

Combine like terms: 2x + x = 3x
36 + 3x + -2y + y = 180

Combine like terms: -2y + y = -1y
36 + 3x + -1y = 180

Solving
36 + 3x + -1y = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + 3x + -36 + -1y = 180 + -36

Reorder the terms:
36 + -36 + 3x + -1y = 180 + -36

Combine like terms: 36 + -36 = 0
0 + 3x + -1y = 180 + -36
3x + -1y = 180 + -36

Combine like terms: 180 + -36 = 144
3x + -1y = 144

Add 'y' to each side of the equation.
3x + -1y + y = 144 + y

Combine like terms: -1y + y = 0
3x + 0 = 144 + y
3x = 144 + y

Divide each side by '3'.
x = 48 + 0.3333333333y

Simplifying
x = 48 + 0.3333333333y

See similar equations:

| 2x+36-2y+x+7=180 | | 1/w-1-1/5w-5=4/5w-5 | | (4h-3)-(2h-8)= | | 33-7(n)=9075 | | y=220x^2+25x | | -4+10x-4x^2=0 | | 18069333.33333=(1/3)(440^2*x) | | 5x-12=16-12x | | (x-5)(x-6)=x^2+3x+7 | | 4(n-4)=1+5n | | y-4=6(x-6) | | x(a-b)-x(a+b)+4b^2=0 | | 63-7x=2x+16 | | 4w+3=-7 | | 4w+3=7 | | y=6-3 | | 2t-3=-3t+2 | | x*x+14=1887 | | -2(2x-5)=-3+7-x+3 | | 9x^2-54x-1=0 | | x+(x-30.2)+(x+25.7)=197.1 | | 3x^2-2kx-k+8=0 | | x+5=-3x+7 | | 1+1=x^2 | | (M-4)(m-6)(m-3)/(m-2)(m-12)(2m-3) | | 1x+1/3x=8 | | If+3I=2f+4 | | 5e/2=-2 | | 1/3/4 | | 2a(b+3c-4d)= | | 2x^2+5x+25/4=57/4 | | 18x^2+38x+20=0 |

Equations solver categories